Fabric and Garment Drape Measurement - Part 1 (Journal of Fiber Bioengineering and Informatics, 2012)
This paper aims to make a comprehensive review of measurement methods developed for evaluatingfabric and garment drape. Drapemeters used for evaluating drapeability since Pierce's bending lengthtester are reviewed. Parameters proposed for measuring drapeability are also considered. The authorspropose that using flat fabric methods does not accurately reflect the drape of fabrics when worn. Thepaper is a pre-cursor to a new image analysis technique which will be reported in Part 2.